2021
DOI: 10.1002/pc.26033
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐friendly polymer composites: A review of suitable methods for waste management

Abstract: The amount of residues generated by agriculture, industrial, or urban activities continuously increases and, consequently, demands several methods for their correct management. The incorrect disposal can cause, in specific cases, environmental contamination by heavy metals or leaching as well as promote the spread of diseases as insect proliferation. Commonly, landfilling, incinerating, composting, or energy/fuel generation can control the disposal or reuse of residues. Among the methods for the reuse of waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 248 publications
(296 reference statements)
1
21
0
Order By: Relevance
“…Elongation normally decreases with fiber content, which is generally associated with an increase in stiffness and strength, sometimes even impact strength of the composite increases with fiber content. [4] In this study, a reduction in elongation of the samples with the addition of PFW also indicated greater matrix stiffness.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Elongation normally decreases with fiber content, which is generally associated with an increase in stiffness and strength, sometimes even impact strength of the composite increases with fiber content. [4] In this study, a reduction in elongation of the samples with the addition of PFW also indicated greater matrix stiffness.…”
Section: Resultssupporting
confidence: 52%
“…This test is also important to evaluate the quality of the leather used, according to their extrinsic characteristics during the wet blue stage. [4] The results of dry and wet tear strength test are shown in Figure 6. The dry tear strength, in Figure 6A, decreased with the increase in PFW content in the material.…”
Section: Resultsmentioning
confidence: 99%
“…Plastics can be recycled with eco-friendly and simple physical and mechanical methods [35]. Recycling is accomplished by collecting and washing plastic waste, converting it into flakes and granules through pulverization, and then melt processing it by drying and extrusion [36].…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about the environmental impact of fiber production and subsequent disposal operations have grown in prominence as demand for fabrics has increased. Several recent studies show that the textile industry endangers freshwater and atmosphere micro-systems due to the use of industrially harmful and toxic chemicals during the manufacturing process, as well as the release of these chemicals [4][5][6]. Inadequate collection and careless disposal of solid waste pollutes the land and air, endangering human health and the environment.…”
Section: Introductionmentioning
confidence: 99%